1996
DOI: 10.1164/ajrccm.154.5.8912733
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to bacteria in swine-house dust and acute inflammatory reactions in humans.

Abstract: Inhalation of swine-house dust may cause an acute airway inflammatory condition (organic dust toxic syndrome). Thirty-eight healthy subjects were exposed to swine dust while weighing swine for 3 h. We studied the correlation between acute health effects and the inhaled bacterial exposure markers peptidoglycan (the main constituent of the cell walls of gram-positive bacteria, but also present in lesser amounts in gram-negative bacteria) and lipopolysaccharides (LPS; present only in gram-negative bacteria). LPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 22 publications
0
87
2
Order By: Relevance
“…Studies have shown that peptidoglycan is toxic to hamster tracheal epithelium in vitro (Cookson et al, 1989), and this macromolecule also induces reactions that are equivalent to most of the major signs and symptoms associated with bacterial infections, such as fever, leukocytosis, acute-phase responses, and lymphocyte activation (Hauschildt and Kleine, 1995). Furthermore, Zhiping et al (1996) found that the levels of muramic acid (used as a marker of peptidoglycan) in swine-house dust were correlated with granulocyte counts and body temperature in humans who inhaled the dust. Other investigators have reported that dusty indoor environments in schools are associated with adverse health effects (Smedje and Norba¨ck, 2001) and that elevated levels of endotoxin in household surroundings are connected with increased severity of asthma (Michel et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that peptidoglycan is toxic to hamster tracheal epithelium in vitro (Cookson et al, 1989), and this macromolecule also induces reactions that are equivalent to most of the major signs and symptoms associated with bacterial infections, such as fever, leukocytosis, acute-phase responses, and lymphocyte activation (Hauschildt and Kleine, 1995). Furthermore, Zhiping et al (1996) found that the levels of muramic acid (used as a marker of peptidoglycan) in swine-house dust were correlated with granulocyte counts and body temperature in humans who inhaled the dust. Other investigators have reported that dusty indoor environments in schools are associated with adverse health effects (Smedje and Norba¨ck, 2001) and that elevated levels of endotoxin in household surroundings are connected with increased severity of asthma (Michel et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The exposure-response relation found was more pronounced for total dust exposure than for endotoxin or glucan exposure alone, suggesting that other currently unidentified agentsfor instance peptidoglycans-in the dust, besides endotoxin and glucan, may also play a part. 35 The availability of repeated exposure and NAL measurements allowed calculation of variance components between and within subjects, where the variance between subjects reflects differences between people and the variance within subjects the day to day variation within a person. Our data showed that between and within subject variability was not the same for each NAL marker, as the total variance for IL6 and total cell concentrations was larger than for IL8 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Yet little information on bioaerosols is available. This lack of knowledge impedes the understanding of the bioaerosol-related respiratory diseases etiology (3,18,46). Indeed, the airway mucosa is a primary entry site for toxic and pathogenic factors, but what the workers are exposed to and how it impacts respiratory health are poorly addressed.…”
mentioning
confidence: 99%